2013
DOI: 10.2350/13-08-1359-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Microtomographic Analysis of Lower Urinary Tract Obstruction

Abstract: Prenatal obstruction of the lower urinary tract may result in megacystis, with subsequent development of hydro-ureter, hydronephrosis, and renal damage. Oligo- or anhydramnios, pulmonary hypoplasia, and prune belly syndrome are lethal consequences. Causes and mechanisms responsible for obstruction remain unclear but might be clarified by anatomic study at autopsy. To this end, we employed 2 methods of tomographic imaging—optical projection tomography and contrast-enhanced microCT scanning—to elucidate the anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Imaging of a multicystic dysplastic kidney revealed cysts of varying sizes with histological confirmation. Another study demonstrated imaging of lower urinary tract obstruction using contrast-enhanced micro-CT. 49 Cystic kidney disorders have variable inheritance patterns, with a wide variation in recurrence risk. With further optimization, micro-CT may be able to provide a non-invasive, permanent record of disease phenotype in such cases without the need for a full autopsy.…”
Section: Chest and Cardiacmentioning
confidence: 99%
“…Imaging of a multicystic dysplastic kidney revealed cysts of varying sizes with histological confirmation. Another study demonstrated imaging of lower urinary tract obstruction using contrast-enhanced micro-CT. 49 Cystic kidney disorders have variable inheritance patterns, with a wide variation in recurrence risk. With further optimization, micro-CT may be able to provide a non-invasive, permanent record of disease phenotype in such cases without the need for a full autopsy.…”
Section: Chest and Cardiacmentioning
confidence: 99%
“…The main strength of this study is the in‐vivo nature of the measurements and our novel approach to the future development of fetal‐therapy instruments. Studying the intact urinary tract (as opposed to postmortem work‐ups 11 ) in vivo preserves its true shape and anatomical relationships to other pelvic organs, and therefore gives real clinical meaning to the biometric study. The main technical limitation of this study is the small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Standard settings were used for imaging of craniofacial bones (Vora et al, 2016 ). For human soft tissue imaging using the microCT, tissues were first stained with PTAH (phosphotungstic acid-hematoxylin) as previously described (Siebert et al, 2013 ). Raw OPT and microCT scan data were reconstructed using NRecon V1.6.9.4 software (Skyscan, Belgium) and imported into the Drishti Volume Exploration software V 2.6.1 for 3D rendering and image capture.…”
Section: Methodsmentioning
confidence: 99%